Improvement of Recruitment and Selection of Employee Performance of PT. Snepac Shipping - Maulina, Nadia; Dihan, Fereshti Nurdiana (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2023)
This study aims to analyze the improvement of the recruitment and selection system that affects the performance of PT. Snepac Shipping. Qualitative descriptive research is conducted by conducting process observations and interviews with the human resources team at PT. Snepac Shipping. The study lasted six months (January–June 2022), and all results were analyzed descriptively. As a result, when PT. Snepac Shipping needs employees to fill vacant positions, and the human resources department team provides information through employees of PT. Snepac Shipping and wall magazine, and then applicants will send their curriculum vitae via email to the human resources department or send them directly to the office of PT. Snepac Shipping. The selection process involves choosing candidates from a curriculum vitae that satisfies the requirements of the employee position, conducting interviews, and evaluating how promptly applicants show up for interviews. Performance changes are made by comparing the selection process before and after. As a result, the recruitment and selection process affect the performance of PT. Snepac Shipping by reviewing the sound changes in employee activities from passive to active and the faster completion time of each task. In the future, further research related to the relationship between improvement in each component and employee performance in each division is needed. This ensures that each task and responsibility meet the selected employee’s criteria.